Adherence to disease-modifying therapies among patients with multiple sclerosis in Bulgaria - A real world study - Yoana Seitaridou; Teodora Chamova; Maria Kamusheva (Pensoft Publishers, 2024)
Introduction: The purpose was to assess the level of medication adherence (MA) and related factors among individuals with multiple sclerosis (MS) in Bulgaria. Materials and methods: A prospective one-year study was conducted among 54 patients with MS diagnosed, treated, and monitored in Clinic of Neurology, University Hospital "Alexandrovska", Sofia in 2022/2023. Clinical data, patients reported outcomes, patients' characteristics such as age, gender and reduced work capacity, and other data were collected to define the predictors of non-adherence to medicines. MA level was assessed through a free Morisky-Green 4-item questionnaire. Results: Мost of the observed patients were rated with high and moderate adherence to MS therapy (n = 44; 81.48%). The remaining 18.52% of the patients with poor adherence to therapy were women. There was no statistical basis for asserting differences in adherence levels among the various factors considered. Conclusion: The current study demonstrates the importance of MA assessment and provides insights into MA among patients with MS in Bulgaria. Still, there are low-adherent patients, and the responsible factors should be further investigated.